2019
DOI: 10.1111/iju.13917
|View full text |Cite
|
Sign up to set email alerts
|

Complications and reoperations after laparoscopic radical cystectomy in a Japanese multicenter cohort

Abstract: Objectives To describe the complications and their surgical management after laparoscopic radical cystectomy in a Japanese multicenter cohort. Methods The participants were drawn from a retrospective multicenter study at 10 institutions. We identified 436 patients who underwent laparoscopic radical cystectomy with no robot assistance. Early and late complications were graded according to their Clavien–Dindo classification. The records of all patients who underwent surgical interventions for laparoscopic radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…In the present study, Kanno et al . investigated oncologic outcomes and recurrence patterns after LRC using a substantial number of bladder cancer patients ( n = 411) from a multicentric cohort . After a median follow‐up period of 23 months, 2‐year recurrence‐free, cancer‐specific and overall survival rates were 71.0%, 84.7% and 80.1%, respectively, which were comparable to those of open radical cystectomy previously reported.…”
supporting
confidence: 61%
“…In the present study, Kanno et al . investigated oncologic outcomes and recurrence patterns after LRC using a substantial number of bladder cancer patients ( n = 411) from a multicentric cohort . After a median follow‐up period of 23 months, 2‐year recurrence‐free, cancer‐specific and overall survival rates were 71.0%, 84.7% and 80.1%, respectively, which were comparable to those of open radical cystectomy previously reported.…”
supporting
confidence: 61%
“…This study was approved by the institutional review board of Kyoto University Hospital. A common database template was created, and data were collected retrospectively, as previously described 10 . The methods used in laparoscopic cystectomy, as well as the presence or absence and extent of lymph node dissection, were determined based on the policies of each institution.…”
Section: Methodsmentioning
confidence: 99%
“…Complications were reported according to the modified Clavien–Dindo classification system 10 . Ureteroenteric stricture was diagnosed when there was evidence of obstruction on imaging, such as symptomatic hydronephrosis, worsening renal function and/or infection, and worsening hydronephrosis that required surgical intervention.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Kanno et al. observed that, in a total of 411 patients treated by laparoscopic radical cystectomy, 28 (7%) developed local recurrence in the cystectomy bed, and 17 (4%) developed abdominal recurrence including peritoneal carcinomatosis or port site recurrence . When those recurrence cases were combined into a single group, because tumor dissemination during surgical manipulation might cause this type of recurrence, prolonged surgical time was a significant risk factor, in addition to an advanced pathological stage, positive surgical margin and variant histology based on uni‐ and multivariate models.…”
mentioning
confidence: 74%